Electromechanically reconfigurable optical nano-kirigami - Shanshan Chen (Nature Portfolio, 2021)
The authors present on-chip and electromechanically reconfigurable nanokirigami with optical functionalities. 3D deformations are achieved via attractive electrostatic forces between a gold nanostructure layer and silicon substrate, resulting in optical reconfigurations with high modulation contrast and small unit size.